Governing resilient landscapes across the source-to-sea continuum - Welling, R.; Filz, P.; Dalton, J.; Smith, Mark; Silva, J. de; Manyara, P. (Informa UK Limited, 2021)
The source-to-sea continuum links the interconnected ecosystems of the water cycle with the associated socioeconomic processes, demands and pressures. Maximizing benefits and protecting existing resources through integrated water management and governance at scale capitalizes on existing institutional and governmental asymmetries by developing an outcome-driven management that builds on existing local, national and transboundary legal frameworks to enhance connectivity. This paper presents how to action this through focusing on three areas of governance: benefit-sharing dialogues for shared visioning; a multi-stakeholder platform to increase coordination in decision-making both up- and downstream; and improved agency coordination between basins and coasts.